EFEKTIVITAS REDW STRATEGY DAN KEMAMPUAN KOSAKATA TERHADAP KEMAMPUAN MEMBACA DALAM READING CLASS ACTIVITY - System, Administrator; -, Putu Ayu Paramita Dharmayanti; -, Dewa Ayu Ari Wiryadi Joni (Sphota : Jurnal Linguistik dan Sastra, 2015)
Abstract This study focused on investigating the main effect of REDW on studentsâ reading competency and the differential affect of REDW between the students with good vocabulary mastery and with poor vocabulary mastery on studentsâ reading competency in EESP of Unmas Denpasar. The findings show that the students taught using REDW achieved better reading competency than those who were taught using conventional teaching.  Furthermore, there is an interactional effect between teaching strategies and vocabulary mastery on studentsâ reading competency. The students with good vocabulary mastery improved their reading competency when being taught using REDW than using conventional teaching. And also there is difference in reading competency between the students who have poor vocabulary mastery taught with REDW and with conventional study. It can be concluded that this study provides an empirical evidence of the importance of the teaching strategy considering vocabulary mastery in English reading instructions.     Keywords: MCSR, vocabulary mastery, reading competency